Sarkopenia sebagai Faktor Risiko Varises Esofagus Risiko Tinggi berdasarkan Stratifikasi Child-Pugh Pasien Sirosis Hati - Sepmeitutu, Iwandheny; Kurniawan, Juferdy; Maulahela, Hasan; Rinaldi, Ikhwan; Shatri, Hamzah; Pramana, Triyanta Yuli; Makmun, Dadang; Lesmana, Cosmas Rinaldi A; Hidayat, Rudy; Laksmi, Purwita Wijaya; Sunardi, Diana (Jurnal Penyakit Dalam Indonesia, 2024)
Background The high prevalence of sarcopenia in chronic liver disease negatively impacts the quality of life and increases the risk of various complications of cirrhosis, one of which is the development of esophageal varices. The aim of this study was to determine the prevalence of sarcopenia in cirrhosis patients based on the severity of liver cirrhosis and to explore the association of sarcopenia with high-risk esophageal varices stratified by Child-Pugh. Methods This observational cross-sectional study involved patients with liver cirrhosis at Cipto Mangunkusumo Hospital between January and September 2023. Sarcopenia was defined as a reduction in muscle mass accompanied by decreased grip strength or walking speed, according to the AWGS 2019 criteria (Asian Working Group for Sarcopenia). Multivariate logistic regression analysis was conducted to evaluate the association between sarcopenia and high-risk esophageal varices. Results A total of 155 patients with liver cirrhosis were included in this study. The majority of liver cirrhosis patients were males, with hepatitis B being the most commonly found etiology. The prevalence of sarcopenia was found in 40.0% of Child-Pugh A patients, 53.8% of Child-Pugh B patients, and 50.0% of Child-Pugh C patients with a p-value of 0.411. The high-risk of esophageal varices was found more frequently in Child-Pugh B (53.8%) and Child-Pugh C (50.0%) compared to Child-Pugh A (25.6%) with a p-value of 0.013. Bivariate analysis showed that the presence of sarcopenia in liver cirrhosis patients has a statistically significant association with an increased risk of high-risk esophageal varices, especially in the Child-Pugh B and C subgroups of liver cirrhosis patients (OR = 7.50 (95% CI: 1.48 – 37.91, p<0.030)). However, no association was found between sarcopenia and high-risk esophageal varices in the Child-Pugh A subgroup (OR = 1.46 (95% CI: 0.65 – 3.29, p<0.477)). Conclusion Sarcopenia significantly increases the risk of high-risk esophageal varices in liver cirrhosis, especially in those with Child-Pugh B and C classification.